2023
DOI: 10.1038/s43856-022-00228-y
|View full text |Cite
|
Sign up to set email alerts
|

A multistakeholder approach to innovations in NAFLD care

Abstract: Non-alcoholic fatty liver disease (NAFLD) is highly prevalent globally and requires multidisciplinary care. Here, we report key findings of a NAFLD care workshop, address knowledge gaps and highlight a path to optimise healthcare resource use, to improve outcomes in patients with steatotic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…In the primary care setting, NITs with cut‐offs suggestive of hepatic fibrosis 108,109 could inform general practitioners on the risk for prevalent and incident heart disease in patients with suspected MASLD or heart disease and as a result, initiate preventive actions or refer for a cardiovascular workup in specialty care (Figure 3). 9,110–113 Although the current NITs are better at ruling out than ruling in hepatic fibrosis and their accuracy can be affected by concurrent T2D, 83,114 their determination would allow for the initiation of referral pathways based on age, sex, comorbidities and physical signs and symptoms of heart disease and could therefore be a convenient tool to initiate a personalized diagnostic path 16,35,36,115 …”
Section: Considerationsmentioning
confidence: 99%
“…In the primary care setting, NITs with cut‐offs suggestive of hepatic fibrosis 108,109 could inform general practitioners on the risk for prevalent and incident heart disease in patients with suspected MASLD or heart disease and as a result, initiate preventive actions or refer for a cardiovascular workup in specialty care (Figure 3). 9,110–113 Although the current NITs are better at ruling out than ruling in hepatic fibrosis and their accuracy can be affected by concurrent T2D, 83,114 their determination would allow for the initiation of referral pathways based on age, sex, comorbidities and physical signs and symptoms of heart disease and could therefore be a convenient tool to initiate a personalized diagnostic path 16,35,36,115 …”
Section: Considerationsmentioning
confidence: 99%
“…2,3 However, each metabolic disorder has distinct characteristics, resulting in several subtypes of patients requiring a personalized and multidisciplinary approach. 11…”
Section: Introductionmentioning
confidence: 99%
“…Patients with type 2 diabetes mellitus (T2DM) represent a population with a higher risk of NAFLD compared with the general population, and several studies have demonstrated a bidirectional relationship between these two metabolic conditions. Indeed, the presence of T2DM in patients with NAFLD leads to a higher risk of progression towards NASH, advanced fibrosis and hepatocellular carcinoma as well as a higher risk of cardiovascular complications 1 . Furthermore, cardiovascular disease (CVD) represents the leading cause of mortality in patients affected with NAFLD beyond liver‐related complications 2 …”
mentioning
confidence: 99%
“…These important gaps between recommended optimal control of cardiovascular risk using evidence‐based therapies and current management of these patients call for action to close these gaps and require a multistakeholder approach to prevent therapeutic inertia and improve clinical care of patients with T2DM and NAFLD 1 …”
mentioning
confidence: 99%
See 1 more Smart Citation